Association of fermented milk intake and hypertension: a systematic review - Medina Pérez, Verónica; Orozco González, Claudia Nelly; Zúñiga Torres, Guadalupe (Población y Salud en Mesoamérica, 2018)
The objective of this paper is to identify the intake of fermented milk in hypertensive people in different population in the world in order to know their effects on blood pressure. Methodologically, we developed an electronic search on PubMed database to identify clinical trials on humans for this review. The selected results show that the most fermented type used in the investigations was from Lactobacillus helveticus with bioactives tripeptides added Isoleucine-Proline-Proline and Valin-Proline-Proline (IPP and VPP); also there were used Lactobacillus casei strain Shirota (LcS), Lactobacillus planetarium A7, Lactobacillus casei strain Shirota, and Lactococcus lactis YIT 2027, Lactobacillus casei TMC0409 y Streptococus thermophilus TMC 1543 for the fermented milk. Better blood pressure- lowering effects were reported in those interventions where IPP and VPP tripeptides were used.